Touchplates: Low-Cost Tactile Overlays for Visually Impaired Touchscreen Users - Kane, Shaun; Morris, Meredith Ringel; Wobbrock, Jacob O. (Proceedings of ASSETS 2013, 2013)
Adding tactile feedback to touch screens can improve their accessibility to blind users, but prior approaches to integrating tactile feedback with touch screens have either offered limited functionality or required extensive (and typically expensive) customization of the hardware. We introduce touchplates, carefully designed tactile guides that provide tactile feedback for touch screens in the form of physical guides that are overlaid on the screen and recognized by the underlying application. Unlike prior approaches to integrating tactile feedback with touch screens, touchplates are implemented with simple plastics and use standard touch screen software, making them versatile and inexpensive. Touchplates may be customized to suit individual users and applications, and may be produced on a laser cutter, 3D printer, or made by hand. We describe the design and implementation of touchplates, a “starter kit” of touchplates, and feedback from a formative evaluation with 9 people with visual impairments. Touchplates provide a low-cost, adaptable, and accessible method of adding tactile feedback to touch screen interfaces.